Intergovernmental Grants Systems and Management : Applications of a General Framework to Indonesia - Searle, Bob (IMF Working Papers; Working Paper ;, 2002)
Intergovernmental equalization grants have been described as 'the glue that holds a nation together.' Getting the grants system right is critical to countries as they decentralize. This paper illustrates general principles with an example based on Indonesia in 2000. A general grant should be used to supplement own revenues and to finance local service provision where there are no central mandates. The special needs of backward regions would be better provided for by specific grants. Specific grants need to be taken into account in the general grants scheme.